2008
DOI: 10.1038/ijo.2008.234
|View full text |Cite
|
Sign up to set email alerts
|

New ligands for melanocortin receptors

Abstract: Named originally for their effects on peripheral end organs, the melanocortin system controls a diverse set of physiological processes through a series of five G-protein-coupled receptors and several sets of small peptide ligands. The central melanocortin system plays an essential role in homeostatic regulation of body weight, in which two alternative ligands, a-melanocytestimulating hormone and agouti-related protein, stimulate and inhibit receptor signaling in several key brain regions that ultimately affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 100 publications
(82 reference statements)
0
19
0
1
Order By: Relevance
“…Melanocortin receptor pharmacology is complex, with two antagonists/inverse agonists (AgRP and agouti signaling peptide) and MSH ligands that exhibit varying degrees of receptor specificity (Figure 1B; Cone et al, 1996). Other ligands and cell-surface proteins have been identified that regulate melanocortin signaling (e.g., melanocortin receptor accessory proteins 1 and 2, mahogany, mahoganoid, attractin-like protein, syndecans, ion channels and defensins) (Kaelin et al, 2008; Nix et al, 2013, 2015; Anderson et al, 2016). …”
Section: An Overview Of the Central Nervous Melanocortin Systemmentioning
confidence: 99%
“…Melanocortin receptor pharmacology is complex, with two antagonists/inverse agonists (AgRP and agouti signaling peptide) and MSH ligands that exhibit varying degrees of receptor specificity (Figure 1B; Cone et al, 1996). Other ligands and cell-surface proteins have been identified that regulate melanocortin signaling (e.g., melanocortin receptor accessory proteins 1 and 2, mahogany, mahoganoid, attractin-like protein, syndecans, ion channels and defensins) (Kaelin et al, 2008; Nix et al, 2013, 2015; Anderson et al, 2016). …”
Section: An Overview Of the Central Nervous Melanocortin Systemmentioning
confidence: 99%
“…1B) illustrates the collaboration patterns between 10 top clusters consisting of 1903 authors representing 29.6% of the field. Some influential authors (only one per cluster is listed here due to space limitation) are listed in the following in alphabetical order together with their respective fields of research: BARSH GS (mammalian pigmentation [1,2]), FISHER DE (melanoma [3]), HEARING VJ (melanogenesis [4]), STURM RA (human pigmentation [5][6][7]), KAYSER M (prediction [8]), PAUS R (hair follicle [9]), REES JL (evolution [10]), SHRIVER MD (evolution [11,12]), SOUFIR N (melanoma [13]), SPRITZ RA (vitiligo [14]). These figures demonstrate the variety of research areas involved in human pigmentation genetics some of which we discuss below.…”
Section: Setting the Scene: Human Pigmentation Genetics -The Field Anmentioning
confidence: 99%
“…Studies of additional cheetah samples will a Expression levels are given as tags per million reads of an EDGE library prepared from RNA of a black spot or yellow background area of cheetah skin. The genes shown here were chosen based on their roles in pigment cell biology; six are well-established melanocyte transcriptional targets downstream from MC1R signaling (Kobayashi et al 1995;Lamoreux et al 1995;Chintala et al 2005;April and Barsh 2006;Le Pape et al 2009); four encode secreted factors that act upstream, either as ligands or to modify ligands of the MC1R Enshell-Seijffers et al 2008;Kaelin et al 2008); and one, MITF, encodes a transcription factor required for melanocyte development (Steingrímsson et al 2006). The expected direction, increase (+) or decrease (À), for expression level change of each gene is given according to when pigment production switches from yellow pheomelanin to black eumelanin.…”
Section: à4mentioning
confidence: 99%